A multidisciplinary collaborative model based on single-port thoracoscopy for the treatment of giant mediastinal lymph node hyperplasia: a case report. Issue 12 (December 2021) - Gu, Haihua; Liu, Tianshu; Zhu, Ling; Zhao, Lufeng; Fan, Junqiang
Mediastinal unicentric Castleman disease (UCD) frequently manifests as a hyper-enhancing lymph node mass and is often surgically curable. However, because of excessive vascularisation and adhesion to important surrounding structures, surgery is often associated with severe haemorrhage that is often difficult to control thoracoscopically. Therefore, thoracotomy is often preferred, which increases the trauma to the patient and affects postoperative recovery. Here, we describe the case of a 30-year-old male patient with a large upper mediastinal lymph node (7 × 5 × 4 cm) that was compressing his superior vena cava. The distribution of nutritive arteries of the mass was analysed in detail, and the main branches were embolised prior to surgery. With the assistance of preoperative isovolumetric haemodilution, we achieved complete resection through single-port thoracoscopy, with only minor haemorrhage, which enabled the patient to recover rapidly. This multidisciplinary collaborative model, based on single-port thoracoscopic surgery, may be of wide practical use for the treatment of mediastinal UCD.